Leader Strategies in Overcoming Employee Productivity Challenges: Analysis in the Regional Financial Organization Environment: Strategi Pemimpin dalam Menanggulangi Tantangan Produktivitas Karyawan: Analisis di Lingkungan Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Lahat - Amaludin (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Abstract This research aims to analyze the strategies implemented by leaders in overcoming challenges to employee productivity in the context of the Regional Financial Organization. The study focuses on the Financial Management and Asset Agency of Lahat Regency. A qualitative research method was employed, utilizing observation, interviews, and documentation. The results indicate that the leader's role in enhancing employee work ethic is satisfactory, although some challenges persist. Leaders have implemented effective communication strategies, set positive examples, and actively engaged in problem-solving. The implications of these strategies are evident in the improvement of employee discipline and motivation. Keywords : Leadership, Employee Productivity, Regional Financial Organization, Leader's Strategy, Work Ethic